DEAD-Box RNA Helicases in Cell Cycle Control and Clinical Therapy - Lu Zhang; Xiaogang Li (Cells, 2021)
Cell cycle is regulated through numerous signaling pathways that determine whether cells will proliferate, remain quiescent, arrest, or undergo apoptosis. Abnormal cell cycle regulation has been linked to many diseases. Thus, there is an urgent need to understand the diverse molecular mechanisms of how the cell cycle is controlled. RNA helicases constitute a large family of proteins with functions in all aspects of RNA metabolism, including unwinding or annealing of RNA molecules to regulate pre-mRNA, rRNA and miRNA processing, clamping protein complexes on RNA, or remodeling ribonucleoprotein complexes, to regulate gene expression. RNA helicases also regulate the activity of specific proteins through direct interaction. Abnormal expression of RNA helicases has been associated with different diseases, including cancer, neurological disorders, aging, and autosomal dominant polycystic kidney disease (ADPKD) via regulation of a diverse range of cellular processes such as cell proliferation, cell cycle arrest, and apoptosis. Recent studies showed that RNA helicases participate in the regulation of the cell cycle progression at each cell cycle phase, including G1-S transition, S phase, G2-M transition, mitosis, and cytokinesis. In this review, we discuss the essential roles and mechanisms of RNA helicases in the regulation of the cell cycle at different phases. For that, RNA helicases provide a rich source of targets for the development of therapeutic or prophylactic drugs. We also discuss the different targeting strategies against RNA helicases, the different types of compounds explored, the proposed inhibitory mechanisms of the compounds on specific RNA helicases, and the therapeutic potential of these compounds in the treatment of various disorders.